Utilização de Ureia Agrícola e Ureia e Liberação Lenta Combinados com Doses de Nitrogênio na Produção do Capim Massai - Oliveira, Ana Kassia Ribeiro de (Universidade Federal do Tocantins, 2023)
The experimente was conducted on 16 December 2015 to 29 January 2016. The objective of this research was to evaluate the fonts (urea agricultural and urea of slow liberation) and doses (40 kg-1 e 100 kg-1 de N). The delineamento was casualisado entirely with four treatments and three repetitions in outline of factorial arrangement 2 x 2 with two variation sources: doses and fonts of nitrogen. It was accomplished evaluations of productive characteristics as the agronomic and structural characteristics. The rest period went smaller for the dose of 100 kg-1 N with period 35 days. The Mass dries available total and mass dries of sheet to foliate they were not influenced by the doses and sources of nitrogen, the relative value of sheet to foliate, stem and dead material, where for stem and dead material had effect in the increase in the dose of 100 kg-1 N with medium values of 11,37 and 3,51 respectively, and the sheet to foliate it presented better results for to smallest dose 40 kg-1 N with medium value of 96,24. The relationship leafs stem had significância for dose of nitrogen 40 kg-1, where it presented medium value of 62,62. The tillers density resulted in increase in the dose of 100 kg-1 of N with medium value of 1.975,5. The fonts of nitrogen urea of slow liberation and agricultural urea didn't go decisive factor to increase of production of dry matter, in that sense the dosage of nitrogen produces more answers in the characteristics of the morphologic components as well as in the structural characteristics of the plants.